Kekerasan Dalam Sinetron Di Televisi( Studi Analisis Isi Tentang Adegan Kekerasan Dalam Sinetron Anak Jalanan Eps 145 dan Eps 185 ) - Primaskara, Hanandya; , Agus Triyono, M.Si (2017)
In the midst of globalization era, television is one of the most influential medium for the audience, a wide variety of good information that is educational as well as entertainment can be delivered to audiences through television. Soap opera is one program that is a mainstay for the television station. One of the soap opera that is currently emerging is a soap opera watched Anak Jalanan that aired on RCTI and became patron favorit and always get the highest rating and share. But there are violations that occurred in the soap opera often shows scenes of violence, whether that violence verbal and non-verbal violence. So this is where the role of the Indonesian Broadcasting Commission (KPI) as an independent state has the duty and authority stipulated in the broadcasting law and code of conduct broadcasting (P3 and SPS) as a form of public participation in the field of broadcasting. For the present study was made because in the broadcast, Anak Jalanan soap opera has been admonished by the KPI to reduce the level of violence shown. This study uses a quantitative content analysis method by comparing two episodes, the episode 145 and 185. This study analyzed the difference in violent scenes on Anak Jalanan soap before and after in chided by KPI whether there are differences in the level of violence between episodes 145 and 185 episodes ?. After doing some research, it turn out there was indeed a difference in the level of violence significantly, in episode 145, scene of violence shown by 92, while only two scenes of episode 185, the organizer should not have to wait for a television in the scolds, because it has become an obligation to keep content event. And researcher hopes that this research could be a criticism of the media, especially local television to fix the show, for the parents also to be more selective again in watching it so that the children do not get their hands impact, hereinafter also criticism for the government to be able more firm in taking action against a television program that contains elements of violence.